Edit and read at the University - Valinoti, Beatriz C.; Parada, Alejandro E. (Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2019)
A History of Reading could be defined as many stories still pending. One of the tasks of the field is to build a history of the academic edition and a history of the books stored in the libraries of universities. But how is that story built? What are the knowledge dissemination strategies of the researchers of the Facultad de Filosofía y Letras (Universidad de Buenos Aires)? What do the libraries of the Institutes keep in their memory? How can we reconstruct the testimony of a (possible) reading in the university using the memory of those Institutions? How can the contents of university libraries be used to understand the culture of publishing and reading? What do the new theoretical perspectives on the explanation of reading contribute to these questions? In this context, the present project, Editar y leer en la Universidad. Una historia de la edición académica de la Facultad de Filosofía y Letras (UBA) desde la Historia de la Lectura, aims to look for new keys of interpretation to these questions, acknowledging that this is a valuable opportunity to start the path of rethinking concepts and categories, based on the new trends in Reading History.